Sandblasting and fibronectin-derived peptide immobilization on titanium surface increase adhesion and differentiation of osteoblast-like cells (MC3T3-E1) - Samdharu Pramono; Kamolparn Pugdee; Jintamai Suwanprateep; Sittichai Koontongkaew (Elsevier, 2016)
Background/purpose: Various chemical titanium (Ti) surface modifications have been reported for enhancing cellular activities that promote early osseointegration. The purpose of this study was to determine if sandblasted Ti coated with or without fibronectin (FN) or FN-derived peptides stimulated osteoblast-like cell adhesion, spreading, proliferation, and differentiation. Materials and methods: Osteoblast-like cells (MC3T3-E1) were cultured on sandblasted Ti disks immobilized with FN or FN-derived peptides [GRGDSP (Gly-Arg-Gly-Asp-Ser), PHSRN (Pro-His-Ser-Arg-Asn), or GRGDSP/PHSRN]. Surface topography, cell morphology, cell adhesion, cell proliferation, analysis of osteogenesis-related genes and protein expression, alkaline phosphatase, and alizarin red staining of mineralization were evaluated. Results: The sandblasted Ti coated with FN or FN-derived peptides enhanced cell adhesion and cell proliferation. However, the Ti coated with FN or FN-derived peptides groups were similar in cell spreading. Osteogenic differentiation was observed in the peptide-modified Ti surface groups, compared with that of the noncoated Ti group. FN and GRGDSP/PHSRN coating enhanced the gene and protein expression of Runx2, osteocalcin, and bone sialoprotein. Alkaline phosphatase activity and matrix mineralization were also markedly enhanced in the Ti coated groups. Conclusion: The sandblasted Ti coated with FN or FN-derived peptides (GRGDSP/PHSRN) markedly enhance adhesion, proliferation, and differentiation of osteoblast-like cells compared with uncoated sandblasted Ti.